Análise acústica em brinquedos ruidosos - Taxini, Carla Linhares [UNESP]; Kinoshita, Sérgio Kodi; Guida, Heraldo Lorena [UNESP] (CEFAC Saúde e Educação, 2013)
PURPOSE: to analyze the levels of noise emitted by nationally-sold toys for use by children from 1 to 5 year old; to compare the values among the toys with and without the seal of Inmetro (National Institute of Metrology, Standardization and Industrial Quality) and to analyze the sound spectrum of toys, in order to identify the area of the cochlea that may be more affected by these noises. METHOD: measurements were performed on 20 sound toys (10 with the seal of the Inmetro and 10 without the seal) with the use of digital sound level meter in an acoustically treated room, and the sound analysis was performed using the Praat program. RESULTS: toys placed at 2.5 cm from the equipment with the seal of the Inmetro had an intensity ranging from 61.50 to 91.55 dB (A) and from 69.75 to 95.05 dB (C), positioned at 25 cm ranged from 58.3 to 79.85 dB (A) and from 62.50 to 83.65 dB (C). The results of the toys without warranty stamps placed at 2.5 cm ranged from 67.45 to 94.30 dB (A) and 65.4 to 99.50 dB (C) and the distance of 25 cm recorded from 61. 30 to 87.45 dB (A) and 63.75 to 97.60 dB (C), so that the findings demonstrated that there are noisy toys that go beyond the values recommended by the current legislation in both groups, with and without warranty stamps . CONCLUSION: the toys without the seal of Inmetro showed intensities values significantly higher than the other group, offering more risk to the children s hearing health.

OBJETIVO: analisar os níveis de ruídos emitidos por brinquedos nacionalmente comercializados, utilizados por crianças de 1 a 5 anos; comparar os valores entre os brinquedos com e sem selo do Inmetro (Instituto Nacional de Metrologia, Normalização e Qualidade Industrial) e analisar o espectro acústico dos brinquedos, com o intuito de identificar a área da cóclea que pode ser mais afetada por esses ruídos. MÉTODO: as medições foram realizadas em 20 brinquedos sonoros (10 com o selo do Inmetro e 10 sem o selo) com o uso do decibelímetro digital em sala acusticamente tratada, e a análise dos sons emitidos pelos brinquedos foi realizada por meio do programa Praat. RESULTADOS: a intensidade do ruído dos brinquedos com o selo do Inmetro posicionados a 2,5 cm do equipamento variou de 61,50 a 91,55 dB(A) e 69,75 a 95,05 dB(C) e a referente à distância de 25 cm variou entre 58,30 a 79,85 dB(A) e 62,50 a 83,65 dB(C). A intensidade do ruído dos brinquedos sem o selo do Inmetro a 2,5 cm variou entre 67,45 a 94,30 dB(A) e 65,4 a 99,50 dB(C) e na distância de 25 cm registrou desde 61,30 a 87,45 dB(A) e 63,75 a 97,60 dB(C), portanto os achados demonstraram que existem brinquedos ruidosos que ultrapassam os valores recomendados pela legislação vigente em ambos os grupos, com e sem selo do Inmetro. CONCLUSÃO: os brinquedos sem o selo do Inmetro apresentaram valores de intensidade significantemente maior em relação ao outro grupo, oferecendo maior risco à saúde auditiva das crianças.
Acoustics analysis of the noisy toys
Keywords: Jogos e Brinquedos; Ruídos; Crianças; Perda Auditiva; Play and Playthings; Noise; Children; Hearing Loss